2021
DOI: 10.3390/cancers13133157
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel-Mediated Uptake and Retention of Gold Nanoparticles in Tumor Cells and in Cancer-Associated Fibroblasts

Abstract: Due to recent advances in nanotechnology, the application of nanoparticles (NPs) in cancer therapy has become a leading area in cancer research. Despite the importance of cancer-associated fibroblasts (CAFs) in creating an optimal niche for tumor cells to grow extensively, most of the work has been focused on tumor cells. Therefore, to effectively use NPs for therapeutic purposes, it is important to elucidate the extent of NP uptake and retention in tumor cells and CAFs. Three tumor cell lines and three CAF ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
4
19
0
Order By: Relevance
“…Labelled cell lines were assessed by flow cytometry to measure percent expression and median fluorescent intensity of the FITC signal in monocultures of MIA PaCa-2 and CAF98, vs. in co-cultures of MIA PaCa-2 and CAF98, Figure 3 D, which shows no effect of the co-culture on the GNP uptake of either cell lines. However, the results show that the uptake of GNPs in CAFs is over three times higher than that of cancer cells in both monoculture and co-culture, which is in agreement with our previous experiments that were done in monoculture [ 21 , 22 ]. This is an important observation that might open the door for targeting not only cancer cells but also CAFs using GNPs.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Labelled cell lines were assessed by flow cytometry to measure percent expression and median fluorescent intensity of the FITC signal in monocultures of MIA PaCa-2 and CAF98, vs. in co-cultures of MIA PaCa-2 and CAF98, Figure 3 D, which shows no effect of the co-culture on the GNP uptake of either cell lines. However, the results show that the uptake of GNPs in CAFs is over three times higher than that of cancer cells in both monoculture and co-culture, which is in agreement with our previous experiments that were done in monoculture [ 21 , 22 ]. This is an important observation that might open the door for targeting not only cancer cells but also CAFs using GNPs.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, GNPs were added to the RT protocol since GNPs are successful radiosensitizing agents. There is evidence that GNPs and low concentrations of anticancer drugs can sensitize cancer cells to radiotherapy in an in vitro monoculture environment [ 18 , 19 , 20 , 21 , 22 ]. GNPs enter cells primarily via receptor-mediated endocytosis (RME) [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…These treated cells cannot enter anaphase and remain locked in mitosis and become multinucleate as the nuclear envelope reforms around the multiple asters with DTX dose under 50 nM 39 . These results are consistent with other studies that reported a signi cant increase in GNP uptake with the treatment of DTX in multiple different cell lines 19,39 .…”
Section: Docetaxel Prodrug Lipid Nanoparticles Effects In Vitrosupporting
confidence: 93%
“…Because of this, DTX has been used as a radiosensitizer in several clinical trials [17][18] . Moreover, the defect in the function of MTs leads to signi cant accumulation of GNPs within cells over time 19 . Hence, the coupling of these two radiosensitizers with RT could result in a synergistic therapeutic outcome due to their complementary mechanism of action.…”
mentioning
confidence: 99%
“…As a result, the combination of low dose DTX and GNPs has been explored as an option for combined therapy in two-dimensional (2D) monolayers and in three-dimensional (3D) spheroids, like those found in Fig. 1 26 , 27 . It has been shown that non-toxic doses of DTX can increase the uptake of GNPs, and that the addition of DTX to a GNP treatment leads to a synergistic effect when combined with RT, in monolayer 28 .…”
Section: Introductionmentioning
confidence: 99%